Sakinio nominalizacija, jos esmė ir vaidmuo kalboje - Valeika, Laimutis (Kalbotyra, 1977)
The article deals with theoretical prerequisites for the description of nominalisations (i. e. nominal word-combinations) in Lithuanian. Nominalisation takes place in a discourse. It generally covers central elements of the sentence (i. e. rhematic constituents), which means that central elements of the sentence assume the role of head-word in the corresponding word-combination. The formation of nominal word-combinations (i. e. the process of nominalisation) is stimulated above all by the immediate needs of constructing connected speech.